Design of intelligent cruise control system using fuzzy-PID control on autonomous electric vehicles prototypes - Saputro, Joko Slamet; Anwar, Miftahul; Adriyanto, Feri; Ramelan, Agus; Yusuf, Putra Maulana; Irsyadi, Fakih; Firmansyah, Rendra Dwi; Putri, Tri Wahyu Oktaviana (National Research and Innovation Agency, 2024)
Electric vehicles provide a solution for using alternative fuels, namely, electricity. Electric vehicles are used for short distances and intercity travel over long distances, increasing the risk of accidents. Cruise Control is a technology embedded in vehicles to maintain stable speeds; this system will automatically adjust the vehicle's speed when motion changes cause changes in vehicle speed. This study aims to apply lidar sensors to detect distance in the Intelligent Cruise Control (ICC) system using the Fuzzy-PID control method. Testing results were obtained at safe distance inputs of 5, 6, and 7 meters with various object distances. All the tests were carried out; the response systems were obtained with an average settling time of 5 seconds and an average overshoot of 1.53%. Therefore, the proposed Fuzzy-PID method works well for controlling Intelligent Cruise Control systems in autonomous electric vehicle prototypes.